STUDY OF THE NATURAL WATER TOTAL GROSS COMPOSITION INFLUENCE TO THE ANALYTICAL SIGNAL MAGNITUDE ON TWO JETS PLAZMATRON - Dorzhueva, G.Zh.; Urmanbetov, К.; Tashtanov, R.А. (Recent Contributions to Physics, 2008)
It was study the influence of the natural water gross composition to spectral lines intensity on length of plasma. It installed that the gross composition total content didn’t influence to spectral lines intensity distribution of microelement’s atoms and ions which contained in natural water. It was significant that the calibrating graphs for all atom and ion lines of consider elements coincide to each other in gross composition absence and presence.